Commercial leisure property valuation: A comparison of the case studies in UK and Lithuania - Maliene, Vida; Deveikis, Steponas; Kirsten, Louise; Malys, Naglis (International Journal of Strategic Property Management, 2010)
The development of leisure as an economic activity has come into focus over the last century. Nowadays, a commercial leisure property has gained an important role within the total spectrum of world economies. Despite these developments in the leisure sector, the valuation of property for the purpose of commercial leisure is still regarded as an Achilles’ heel. The accepted approach to the property valuation in UK is to perform an open market valuation for the existing use. However, for the specialized properties including leisure assets, the distinctive valuation methodology has to be applied. This paper outlines the principles of methodology that are commonly used for the valuation of leisure property in the UK, Lithuania and other countries. Factors affecting the valuation process with respect to the property development and investment decision are discussed. The study is accompanied with examples of valuation method applications and analyses of individual case studies of golf course valuation.First Published Online: 18 Oct 2010